If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3y + -2 = 2.26 Reorder the terms: -2 + 3y = 2.26 Solving -2 + 3y = 2.26 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '2' to each side of the equation. -2 + 2 + 3y = 2.26 + 2 Combine like terms: -2 + 2 = 0 0 + 3y = 2.26 + 2 3y = 2.26 + 2 Combine like terms: 2.26 + 2 = 4.26 3y = 4.26 Divide each side by '3'. y = 1.42 Simplifying y = 1.42
| 3(x+5)-2x+12= | | 7(314)-75(21)-2(259)=x(10+5) | | -2.22=m/4-5 | | 3[z-(6z+15)+5]=3(z+2) | | 1.3+2.3=2.3-2.3 | | Y+6+y=28 | | 7(314)-75(21)-2(259)=x(3+5) | | 1.2=4s-11.2 | | -7(x-8)=9-6x | | 11w-81=744 | | -8-5n=64+3 | | -2y^2-14y+7=0 | | 8[5-8(x-1)]+7[(5x+6)-8]=11x-341 | | .8=ln(y) | | 0=x^2+2x-63 | | 4x+4x=7x-9 | | 5y(y-2)=6-3y | | 4.7x+2=3.2x-4 | | 40x+4(1.5x)=736 | | 4(x-6)-(x+2)=-12 | | g/6-17=1 | | 4x-3+2=8x-3-x | | -8+2x=4 | | 16=10-1/4m | | graphy=-x^2+4x-7 | | 3(x+2)=4(x-7) | | g/30-980=-954 | | 3t(t-2)=4-2t | | -4(-2t-4)=-2[2t+3(t+2)] | | (1/7)-n/3=N? | | (1/7)-n/3= | | m/5-1=4 |